Striving to be prepared for the painful: Management strategies following a family member's diagnosis of advanced cancer - Hedberg Berith; Sjolander Catarina; Ahlstrom Gerd (BMC, 2011)
Abstract Background Cancer has consequences not only for the sick person but also for those who have a close relationship with that person. Greater knowledge about how family members manage the situation in the period immediately following the diagnosis means greater opportunity to provide the best possible support for the family. The purpose of this study was to explore management strategies that family members use when the patient is in the early stage of treatment for advanced cancer. Methods Twenty family members of cancer patients were included in the study shortly after the diagnosis. The patients had been diagnosed 8-14 weeks earlier with advanced lung cancer or gastrointestinal cancer. The data were collected in interviews with family members and subjected to qualitative latent content analysis. Through the identification of similarities and dissimilarities in the units of meaning, abstraction into codes and sub-themes became possible. The sub-themes were then brought together in one overarching theme. Results The overall function of management strategies is expressed in the theme Striving to be prepared for the painful. The family members prepare themselves mentally for the anticipated tragedy. Family relationships become increasingly important, and family members want to spend all their time together. They try to banish thoughts of the impending death and want to live as normal a life as possible. It becomes important to family members to live in the present and save their energy for the time when they will need it the most. How participants handle their worries, anxiety and sadness can be categorized into seven sub-themes or management strategies: Making things easier in everyday life, Banishing thoughts about the approaching loss, Living in the present, Adjusting to the sick person's situation, Distracting oneself by being with others, Shielding the family from grief, and Attempting to maintain hope. Conclusions The findings revealed that the family members have their own resources for handling the early stage of the cancer trajectory in an acceptable way. There is a need for longitudinal studies to generate knowledge for designing evidence-based intervention programmes that can prevent future ill-health in these vulnerable family members.